2021
DOI: 10.1021/acs.analchem.0c05082
|View full text |Cite
|
Sign up to set email alerts
|

Electromembrane Extraction and Mass Spectrometry for Liver Organoid Drug Metabolism Studies

Abstract: Liver organoids are emerging tools for precision drug development and toxicity screening. We demonstrate that electromembrane extraction (EME) based on electrophoresis across an oil membrane is suited for segregating selected organoid-derived drug metabolites prior to mass spectrometry (MS)-based measurements. EME allowed drugs and drug metabolites to be separated from cell medium components (albumin, etc.) that could interfere with subsequent measurements. Multiwell EME (parallel-EME) holding 100 μL solutions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The potential of using liver organoids with LC-MS measurements to perform drug metabolism studies has been shown by Skottvoll et al 38 To study the phase I metabolism of heroin to 6-monoacetylmorphine (6-MAM) and morphine, liver organoids were exposed to the drug for 1, 3, 6, and 24 hours, with the concentrations of heroin and 6-MAM tracked during those timepoints. The authors developed an electromembrane extraction approach to separate drug metabolites from components of cell culturing media, allowing for simple and repeatable measurements.…”
Section: Metabolomics Methods For the Analysis Of Organoidsmentioning
confidence: 99%
“…The potential of using liver organoids with LC-MS measurements to perform drug metabolism studies has been shown by Skottvoll et al 38 To study the phase I metabolism of heroin to 6-monoacetylmorphine (6-MAM) and morphine, liver organoids were exposed to the drug for 1, 3, 6, and 24 hours, with the concentrations of heroin and 6-MAM tracked during those timepoints. The authors developed an electromembrane extraction approach to separate drug metabolites from components of cell culturing media, allowing for simple and repeatable measurements.…”
Section: Metabolomics Methods For the Analysis Of Organoidsmentioning
confidence: 99%
“…E) Drug studies performed on chip (single-sample dEME) with continuous EME extraction and no manual sample handling prior to LC-MS analysis (this Communication). Figure adapted/expanded from our previous work [12] (further permissions related to the material excerpted should be directed to the American Chemical Society). solution was continuously pumped through the acceptor channel.…”
mentioning
confidence: 99%
“…We have recently shown that off-line EME is excellent for simple and parallel extraction of drugs and metabolites from organoids in a 96-well format, reducing sample preparation steps (Figure 1D). [12] However, on-line coupling of EME and MS would allow for a substantially higher degree of automation and throughput. EME has been briefly explored for on-line coupling to MS for microsome-based studies, [13][14][15] encouraging us to hypothesize that EME is a potential tool for the bridging of liver organoids and MS.…”
mentioning
confidence: 99%
See 2 more Smart Citations